Analysis of over current relay and hybrid filter including the utilization of SFCL in a distribution network with DG - Saumen Dhara; Pradip Kumar Sadhu; Alok Kumar Shrivastav (AIMS Electronics and Electrical Engineering, 2022)
Recently, as technology advances, demand for electrical energy has increased at an unprecedented rate in the power system network. With the growing importance of renewable energy assets and the global expansion of distributed generation (DG) efficiency, grid fault analysis is critical for increasing the efficiency and resilience of the power system. Apart from fault current, the interconnection of distributed generators in the distribution network results in an increase in system harmonics, as well as a halt in the operation of the overcurrent relay due to backward directed fault current. However, since the SFCL is considered to be more effective when used with distributed generators, the investigation of a protective relay due to the employment of SFCL is particularly necessary as a substitute strategy for limiting fault current in the distribution network. Additionally, many electrical customers continually require quality control, depending on the quality of the grid power it delivers and the performance of the terminal device. However, a variety of external and internal variables have an effect on the quality of energy delivered to the end consumer. Itos similar to fluctuations in tension and frequency, as well as failures. Such power quality concerns erode equipmentos long-term capability and performance. These concerns should be addressed in terms of harmonic reduction via the use of hybrid filtering in order to maximise the efficacy of consumer goods and overall device output. This study proposes a control strategy for the filter to eliminate harmonics and a rectification method for the overcurrent relay employing voltage components for the purpose of applying SFCL, as well as the notion of DG, in a power distribution framework. To validate the suggested approach, a malfunction with an overcurrent relay was simulated using a combination of DG and SFCL. The MATLAB/SIMULINK environment is used to simulate the desired control strategy and see the result.